DETERMINANT OF HOUSING PRICE IN LAGOS RESIDENTIAL MARKET: ROLE OF AGENTS/INTERMEDIARIES. - Olalekan Dimeji Bamiteko; Oyeyemi Omodadepo Adebiyi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
ABSTRACT There is price discrepancy in similar housing goods in different parts of Lagos. Even in the same vicinity, similar housing goods still have different prices. This study investigates the discrepancy by looking at the role the intermediaries play in fixing housing price in Lagos residential market. A survey was carried out in Lagos metropolitan city with 751 respondents (41 producers, 33 intermediary and 677 consumers). The sample was selected through a multistage sampling technique and the data analyzed with descriptive statistic. The study found that there is a game played by the intermediaries in fixing prices. The intermediary often give incomplete information to the house consumers thereby, making the consumers pay more than their expectations. The study concluded that in Lagos residential market, price is influenced by the intermediary as a result of asymmetry information which makes the consumer pay more.